The Islamic Culture of “Wetu Telu Islam” Affecting Social Religion in Lombok - Muliadi Muliadi; Didin Komarudin (el Harakah: Jurnal Budaya Islam, 2020)
This writing is motivated by a very abundant religious culture in Indonesia, including the phenomenon found in Lombok, West Nusa Tenggara which is famous for “Wetu Telu Islam”. It contains the religious system filled with ceremonies and rituals which are accompanied by special symbols that have certain meanings. The method used in this paper is historical descriptive, by systematically explaining the history of the people of Lombok, the cultural patterns of “Wetu Telu Islam”, including its historical figures, doctrine, development, and existence. Then the writer uses structural semiology in analyzing the meaning of symbol elements found in the religious rituals of “Wetu Telu Islam” in Lombok. “Wetu Telu Islam” according to the people of Lombok is a very perfect Islam as it is built from two solid dimensions, namely dzohir and ihsan. For that reason, “Wetu Telu Islam” for them is the teachings of Sufism which emphasize the spirit, and soul. It is the spirit of holistic Islamic teachings, namely: shari’a, thoriqot, haqiqot, and ma‘rifat. Everything is building up, mutually reinforcing, and inseparable.Tulisan ini bermuara dari budaya agama yang sangat berlimpah di Indonesia, termasuk fenomena yang ditemukan di Lombok, Nusa Tenggara Barat yang terkenal dengan “Islam Wetu Telu”. Sistem keagamaan yang terkandung di dalamnya sarat upacara dan ritual yang disertai simbol-simbol khusus bermakna tertentu. Metode yang digunakan dalam makalah ini adalah deskriptif historis, yaitu secara sistematis menjelaskan sejarah masyarakat Lombok, pola-pola budaya “Islam Wetu Telu”, termasuk tokoh sejarah, doktrin, perkembangan dan keberadaannya. Kemudian penulis menggunakan semiologi struktural dalam menganalisis makna elemen simbol yang ditemukan dalam ritual keagamaan “Islam Wetu Telu”di Lombok. “Islam Wetu Telu” menurut masyarakat Lombok adalah Islam yang sangat sempurna karena dibangun dari dua dimensi yang kuat, yaitu dzohir dan ihsan. Karena itu, “Islam Wetu Telu” bagi mereka adalah ajaran tasawuf yang menekankan hati dan jiwa. Ini adalah semangat ajaran Islam holistik, yaitu: syariah, thoriqot, haqiqot, dan ma’rifat. Semuanya membangun, saling menguatkan, dan tak terpisahkan.